To Shape the Future: How Labor Market Entry Conditions Affect Individualss Long-Run Wage Profiles - Beartice Brunner; Andreas Kuhn (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
We study the long-run effects of initial labor market conditions on wages for a large sample of male individuals entering the Austrian labor market between 1978 and 2000. We find a robust negative effect of unfavorable entry conditions on starting wages. This initial effect turns out to be quite persistent and even though wages do catch up later on, large effects on lifetime earnings result. We also show that initial labor market conditions have smaller and less persistent effects for blue-collar workers than for white-collar workers. We further show that some of the long-run adjustment takes place through changes in job-mobility and employment patterns as well as in job tenure. Finally, we find that adjustments at the aggregate level are key to explain wages' adjustment process in the longer run.
Keywords: E3; J2; J3; J6; M5; 330; labor market cohorts; initial labor market conditions; long-run wage profiles; persistence of labor market shocks; unemployment; business cycle